India as a factor in Pakistan-Nepal Relations - Dharamdasani, M (Journal of Political Science, 1998)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Journal of Political Science Vol.1(1) 1998 p.16-24